The Influence of Aid and Income on Persistence at a Small Private College - Charles N. Landreth; Robert O. Riggs (Educational Considerations, 2002)
In the 1990s, many private institutions gave up the practice of making need-blind admission decisions and stopped aiding students to the full extent of their need.